Multimode delivery in the classroom - Dodd, William Steven (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
Because of recent technological advances, subtitling is now easier and more versatile than in the past. There is an increasing interest in the use of digitally-recorded audiovisual materials with both soundtrack and subtitles in the same language as a language-learning aid. The full potential of this is not currently attained because of poor-quality subtitling and less appropriate “caption” or “synopsis” rather than “transcription” subtitles. An adaptation of a format successful over two decades in Europe might be of value for South-East Asian language learners.